Theoretical study of a multichannel plasmonic waveguide notch filter with double-sided nanodisk and two slot cavities - Qi, Yunping; Zhou, Peiyang; Zhang, Ting; Zhang, Xuewei; Wang, Yue; Liu, Chuqin; Bai, Yulong; Wang, Xiangxian (Results in physics, 2019)
Based on the transmission characteristics of surface plasmonic subwavelength structure, a multichannel plasmonic notch filter comprising two slot resonators and a nano-disk cavity with the metal-insulator-metal waveguide is proposed and investigated numerically using the finite element method (FEM). It demonstrates that our proposed structure has the novel multichannel notch filter characteristics in optical regime. And the three resonance trough wavelengths of the notch filter can be tuned by changing the radius of the nano-disk and width of the slot, which is in good agreement with the results of the coupled mode theory (CMT). Moreover, the second resonance trough wavelength of the transmission spectrum increases in almost the same intervals of 30 nm when the radius of nano-disk cavity increases in intervals of 10 nm, showing a Fano line and an obvious red-shift. At the third resonance trough, the results show that the plasmon-induced transparency (PIT) is produced. And the PIT response is strongly influenced by the separation gap between the adjacent slot cavities. Additionally, the FOM* (figure of merit) and sensitivity of this structure can be as high as 99 and 750 nm/RIU, respectively. The results of this study not only present a tunable multichannel plasmonic notch filter, but also aid in developing ultra-compact refractive index sensor in optical highly integration circuits. Keywords: Surface plasmon polaritons, Metal-insulator-metal waveguides, Plasmon-induced transparency, Plasmonic filter